PENERAPAN SANKSI YANG TEPAT TERHADAP PENGGUNA SEPEDA YANG MELANGGAR ATURAN LALU LINTAS - Fransiska Rambu Kudu; Hari Soeskandi (Gapenas Publisher, 2023)
Traffic violations are the problem that often occurs and can endanger other road users’ safety. Along with technological development, the number of bicyclists has also increased. This enhancement became a trigger for violations committed by bicyclists on the highway. The enhancement of bicyclists is not accompanied by a sense of awareness and safety in driving and often ignores the traffic rules that have been settled. Not only that, the lack of a sense of discipline also causes the bicyclists to become perfunctory to the traffic rules. Based on these explanations, the objective of this research is to find out the most appropriate punishment for the bicyclists that break the traffic rules, so they could obey the traffic rules that applied based on the law and how these laws can be applied in society